Short-term plasticity regulates the E/I ratio and the temporal window for spike integration in CA1 pyramidal cells - Bartley, Aundrea F. (Eur J Neurosci, 2015)
Many neurodevelopmental and neuropsychiatric disorders have an imbalance between excitation (E) and inhibition (I) caused by synaptic alterations. The proper E/I balance is especially critical in CA1 pyramidal cells because they control hippocampal output. Activation of Schaffer collateral axons causes direct excitation of CA1 pyramidal cells, quickly followed by disynaptic feed-forward inhibition, stemming from synaptically induced firing of GABAergic interneurons. Both excitatory and inhibitory synapses are modulated by short-term plasticity, potentially causing dynamic tuning of the E/I ratio. However, the effects of short-term plasticity on the E/I ratio in CA1 pyramidal cells are not yet known. To determine this we recorded disynaptic IPSCs and E/I ratio in CA1 pyramidal cells in acute hippocampal slices from juvenile mice. We find that while inhibitory synapses have paired-pulse depression, disynaptic inhibition instead expresses paired-pulse facilitation (≤ 200 ms intervals), caused by increased recruitment of feed-forward interneurons. Although enhanced disynaptic inhibition helps constrain paired-pulse facilitation of excitation, the E/I ratio is still larger on the second pulse, increasing pyramidal cell spiking. Surprisingly, this occurs without compromising the precision of spike timing. The E/I balance regulates the temporal spike integration window from multiple inputs; here we show that paired-pulse stimulation can broaden the spike integration window. Together, we find that the combined effects of short-term plasticity of disynaptic inhibition and monosynaptic excitation alter the E/I balance onto CA1 pyramidal cells, leading to dynamic modulation of spike probability and spike integration window. Short-term plasticity is therefore an important mechanism for modulating signal processing of hippocampal output.